An Integrated Biochemical, Proteomics, and Metabolomics Approach for Supporting Medicinal Value of Panax ginseng Fruits - Kim, So W.; Gupta, Ravi; Lee, Seo H.; Min, Cheol W.; Agrawal, Ganesh K.; Rakwal, Randeep; Kim, Jong B.; Jo, Ick H.; Park, Soo-Yun; Kim, Jae K.; Kim, Young-Chang; Bang, Kyong H.; et al. (Frontiers in Plant Science, 2016)
Panax ginseng roots are well known for their medicinal properties and have been used in Korean and Chinese traditional medicines for 1000s of years. However, the medicinal value of P. ginseng fruits remain poorly characterized. In this study, we used an integrated biochemical, proteomics, and metabolomics approach to look into the medicinal properties of ginseng fruits. DPPH (1,1-diphenyl-2-picrylhydrazyl) and ABTS [2,2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid)] assays showed higher antioxidant activities in ginseng fruits than leaves or roots. Two-dimensional gel electrophoresis (2-DE) profiling of ginseng fruit proteins (cv. Cheongsun) showed more than 400 spots wherein a total of 81 protein spots were identified by mass spectrometry using NCBInr, UniRef, and an in-house developed RNAseq (59,251 protein sequences)-based databases. Gene ontology analysis showed that most of the identified proteins were related to the hydrolase (18%), oxidoreductase (16%), and ATP binding (15%) activities. Further, a comparative proteome analysis of four cultivars of ginseng fruits (cvs. Yunpoong, Gumpoong, Chunpoong, and Cheongsun) led to the identification of 22 differentially modulated protein spots. Using gas chromatography-time of flight mass spectrometry (GC-TOF MS), 66 metabolites including amino acids, sugars, organic acids, phenolic acids, phytosterols, tocopherols, and policosanols were identified and quantified. Some of these are well known medicinal compounds and were not previously identified in ginseng. Interestingly, the concentration of almost all metabolites was higher in the Chunpoong and Gumpoong cultivars. Parallel comparison of the four cultivars also revealed higher amounts of the medicinal metabolites in Chunpoong and Gumpoong cultivars. Taken together, our results demonstrate that ginseng fruits are a rich source of medicinal compounds with potential beneficial health effects.